THE IMPACT OF REHABILITATION MEASURES IN PATIENTS WITH TYPE 2 DIABETES MELLITUS, COMBINED WITH OBESITY ON LIPID PANEL DATA - Sharapa, H. F.; Prokopchuk, V. Yu.; Korobko, L. R.; Hevko, U. P.; Marushchak, M. I. (Rehabilitation and Recreation, 2023)
The purpose of the study was to analyze the impact of the exercise program and therapeutic massage as part of rehabilitation measures in patients with type 2 diabetes mellitus, combined with obesity on lipidograms. Materials and methods. 579 patients with type 2 diabetes mellitus with overweight / obesity who were in hospital in the endocrinology department of Ternopil University Hospital in 2018-2019 were included in the study. 98 of them were with normal body weight, 164 with excessive body weight and 317 with obesity. There was no significant difference between the age and sexual composition between the experimental groups of patients. The concentration of total cholesterol, triacylglycerols, high-density lipoprotein cholesterol were determined by commercially available kits on COBAS 6000 (Roche Hitachi, Germany). Results. 1 month after the rehabilitation measures were carried out in 106 patients with DM2, a normal body weight was established, in 178 - overweight and 295 - obesity, which indicates a decrease in body mass index in patients examined. Durinf analyzing lipid metabolism in type 2 diabetes, depending on the degree of excess body weight in the context of reaching the target levels of lipidogram 1 month after the rehabilitation measures, it was established that as the body weight index increases the number total cholesterol and non high-density lipoprotein cholesterol. When comparing lipidograms, which reached the target levels of lipid in patients with type 2 diabetes, depending on the degree of excess body weight after rehabilitation measures, an increase in the number of patients who reached the target levels of lipidogram indicators, regarding those who did not carry out rehabilitation measures. Accordingly, comparing the percentage of patients whose lipidograms have gone beyond the target values indicates a decrease in their number among those who conducted rehabilitation measures regarding the number of patients without rehabilitation measures. Conclusions. Overweight /obesity affects the severity of lipid metabolism, while increasing body weight index increases the number of patients with DM2 with dyslipidemias, which are characterized by exit beyond the target values of total cholesterol and non high-density lipoprotein cholesterol. Additional appointment in the outhospital period of a complex of rehabilitation measures, which include physical exercises and therapeutic massage, contributes to the increase in the number of patients with DM2 and overweight / obesity, whose lipidograms are within the targets.